2010
DOI: 10.1186/1471-2199-11-84
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of highly conserved Dengue virus sequences with anti-Dengue virus trans-splicing group I introns

Abstract: BackgroundDengue viruses (DENV) are one of the most important viral diseases in the world with approximately 100 million infections and 200,000 deaths each year. The current lack of an approved tetravalent vaccine and ineffective insecticide control measures warrant a search for alternatives to effectively combat DENV. The trans-splicing variant of the Tetrahymena thermophila group I intron catalytic RNA, or ribozyme, is a powerful tool for post-transcriptional RNA modification. The nature of the ribozyme and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 53 publications
0
63
0
Order By: Relevance
“…These ribozymes could be used to treat genetic disorders by repairing the sequence of a mutated mRNA (Sullenger and Cech 1994;Lan et al 1998;Phylactou et al 1998), to selectively kill cancer cells by splicing a sequence that encodes a toxic peptide into cancer-specific mRNAs Kwon et al 2005;Lee et al 2010), and to kill virally infected cells with the same strategy Carter et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These ribozymes could be used to treat genetic disorders by repairing the sequence of a mutated mRNA (Sullenger and Cech 1994;Lan et al 1998;Phylactou et al 1998), to selectively kill cancer cells by splicing a sequence that encodes a toxic peptide into cancer-specific mRNAs Kwon et al 2005;Lee et al 2010), and to kill virally infected cells with the same strategy Carter et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…DENV-2 replication in mosquito cell cultures was suppressed by group 1 splicing introns targeted to the 5ЈCS region (8), and WNV and St. Louis encephalitis virus infections were inhibited in vitro and WNV infection was inhibited in a mouse model by a 5ЈCS-targeting siRNA conjugated to a 41-mer peptide (73). We observed a potent inhibition of YFV and a modest inhibition of WNV by the targeting of their respective 5ЈCS regions.…”
Section: Discussionmentioning
confidence: 66%
“…Initially, a GrpI was identified in the ciliate protozoa Tetrahymena thermophila as a self-splicing intron [76]. Since then GrpI have been used for various applications such as repair of defective mRNA transcripts or as antiviral effectors targeting HIV-1, cucumber mosaic virus, HCV, or DENV1–4 [7779,80**,81**]. A GrpI consists of an external (EGS) and an internal guide sequence (IGS), a trans-splicing domain, and a 3′ exon-of-choice (which can be derived from a pro-apoptotic gene) (Figure 2).…”
Section: Trans-splicing Group I Intronsmentioning
confidence: 99%
“…Carter et al [80**] designed six different GrpI targeting the highly conserved cyclization (CS) sequences (5′CS, CS1, and CS2) in the genomes of DENV1–4. In vitro assays revealed that two of the six GrpI, αDENV-U143-FL and αDENV-U134-FL, targeting U143 and U134 respectively, of the DENV2 5′CS were highly effective, with αDENV-U143-FL being able to cleave the viral RNA of all four DENV serotypes, whereas αDENV-U134-FL was specific to DENV2.…”
Section: Trans-splicing Group I Intronsmentioning
confidence: 99%
See 1 more Smart Citation